Analisa Efisiensi Turbin Uap Berbahan Bakar Fiber Dan Cangkang Sawit Pada Boiler Di PT. Tri Bakti Sarimas Untuk Produksi-Memproduksi Energi Listrik - Karamallah, Rizky; Suwitno, Suwitno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
At this time the need for electrical energy continues to increase, power plants that use non-renewable natural resources are more dominantly used to meet the growing needs of electrical energy. Renewable energy is the solution to this problem. Biomass is a type of renewable energy sourced from living or dead biological materials that can be used as a fuel source in plants. Applications for the use of renewable energy sources in the form of biomass can be analyzed at PT Tri Bakti Sarimas. Where this company uses fiber and palm shell as fuel in boilers. By using fiber and palm shell as renewable fuel in boilers, so as to increase the efficiency value of the turbine. The study used the rankine cycle method to get efficiency values on turbines. From the results of thermal efficiency calculations used can be seen only 33.78% of the power provided into the boiler that can be converted into mechanical energy. At the efficiency value in steam power generation (PLTU) rank for pltu is 25%-50%. The efficiency of the turbine obtained is 33.78% while the efficiency of the generator is 62.5%. the required fibers as much as 7200 kg / hour and palm shells as much as 1800 kg / hour. The resulting turbine power is 2987.97 KW and the electricity generated is 983 KWh.Keyword : rankine cycle, turbine, fiber, palm shell